Existential and religious motifs in L.S. Vygotsky’s essay on “Hamlet” (1916) - Chesnokova M.G., (Культурно-историческая психология, 2018)
In this article existential and religious motifs in the works of young L.S. Vygotsky are considered. The specificity of the existential approach, characterized by blurring the limits of philosophy, science and art and the formation of a synthetic method of cognition of a human being, is emphasized. These features are found in the early works of Vygotsky. The analysis of his essay “The tragedy of Hamlet, prince of Denmark by William Shakespeare” (1916) is the focus of attention. The existential orientation distinguishes both the form and the content of Vygotsky’s work. The genre of the work is a combination of literary criticism and philosophical psychological research. In his essay Vygotsky touches on such existential topics as: the tragedy and loneliness of human existence, existential guilt as the guilt of birth, the issue of formation and self-fulfillment of a man, the relationship of knowledge and action, the dialectic of the external and the internal, the issue of the moduses of human existence — “sinful innocence”, ethical and religious existence, the issue of meaning of life. The parallel between Vygotsky’s existential views, developed in this essay, and the ideas of well-known representatives of the existential approach is drawn. From the existential issues of the play Vygotsky moves on to its inner meaning, which he defines as religious. The four main themes he reveals most fully: the issue of connection between the two worlds — the world of the dead and the world of the living, the issue of sin, punishment and redemption, the issue of darkness of divine Providence (meaning of life) and the issue of overcoming separateness and restoring the unity of the world. In the article the main provisions and principles of study of early Vygotsky and Vygotsky in the period of creation of cultural-historical theory are compared. A continuity between the ideas of Vygotsky’s early works and his latest project of dramatic psychology is observed.